Utilizing Semantic Mapping Strategy to Improve the Reading Comprehension of the Eleventh-Grade Students of SMA Negeri 1 Malinau - Linda Parabak Mangori; Margana Margana (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The objectives of this study were: (1) to describe how the implementation of Semantic Mapping Strategy improves the reading comprehension of eleventh graders at SMA Negeri 1 Malinau, and (2) to determine the extent to which the implementation of Semantic Mapping Strategy improves students’ reading comprehension. This study employed Classroom Action Research (CAR) by adapting the procedures proposed by Kemmis and McTaggart, which include planning, action, observation, and reflection. The participants of this research were eleventh-grade students, with a total of 20 students selected purposively based on preliminary observation indicating that they experienced difficulties in comprehending narrative texts. The research was conducted in two cycles, and the data were collected through reading comprehension tests, observation sheets and interview. The data were analyzed using descriptive quantitative. The findings revealed that the implementation of the Semantic Mapping Strategy was effective in improving students’ reading comprehension of narrative texts. Based on the qualitative data, the strategy created a more interactive, student-centered, and meaningful learning environment, which increased students’ participation, motivation, and confidence during the learning process. Meanwhile, the quantitative data showed a significant improvement in students’ reading comprehension scores, as evidenced by the increase from the pre-test score of 56.75 to the post-test score of 91.5, with all students achieving the minimum mastery criterion (KKTP) in the post-test. In conclusion, the results of this study indicate that the implementation of the Semantic Mapping Strategy is effective in improving students’ reading comprehension of narrative texts at the eleventh grade of the senior high school.